2017
DOI: 10.14393/bj-v33n4a2017-36731
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of common bean and soybean to water stress evaluated at the sitis phenotyping platform

Abstract: ABSTRACT:The great challenge of breeding programs focused on tolerance to water stress is the precise, in large scale, and automated phenotyping. Therefore, the objective of this study was to assess whether the controlled conditions of SITIS Automated Phenotyping Platform and the protocol used are suitable for discriminating cultivars of common bean and soybean for tolerance to this stress. Two experiments were carried out in randomized block design, in a split plot scheme, with four replications. The main plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The amount of water used by the plants can be monitored in each column by the difference in weight. This platform has already been used to evaluate the tolerance to water stress of cotton (GUIMARÃES et al, 2017a), soybean and common bean (GUIMARÃES et al, 2017b) cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of water used by the plants can be monitored in each column by the difference in weight. This platform has already been used to evaluate the tolerance to water stress of cotton (GUIMARÃES et al, 2017a), soybean and common bean (GUIMARÃES et al, 2017b) cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…Data were sent remotely to the cloud and accessible via the internet. In that way, [ 22 ] the system used 100 balances (scales) inside a glasshouse where each one automatically logged weight data every minute. In this study [ 22 ], two common bean cultivars demonstrate greater drought sensitivity compared to soybean cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…In that way, [ 22 ] the system used 100 balances (scales) inside a glasshouse where each one automatically logged weight data every minute. In this study [ 22 ], two common bean cultivars demonstrate greater drought sensitivity compared to soybean cultivars. Thus, it is demonstrated that gravimetric platforms allow recognizing of the effects of biomass accumulation and transpiration per individual plant, as well as calculations related to the TE at the cycle end when seed yield is available.…”
Section: Introductionmentioning
confidence: 99%